Uterine fibroids: an update on current and emerging medical treatment options - Farris M; Bastianelli C; Rosato E; Brosens I; Benagiano G (Dove Medical Press, 2019)
Manuela Farris,1,2 Carlo Bastianelli,1 Elena Rosato,1 Ivo Brosens,3 Giuseppe Benagiano1 1Department of Gynecology, Obstetrics and Urology, Sapienza, University of Rome, Rome, Italy; 2The Italian Association for Demographic Education, Rome, Italy; 3Faculty of Medicine, KU Leuven, Leuven, Belgium Abstract: Uterine fibroids are the most common gynecological disorder, classically requiring surgery when symptomatic. Although attempts at finding a nonsurgical cure date back to centuries, it is only around the middle of the last century that serious attempts at a medical treatment were carried out. Initially, both progestins and estrogen–progestin combinations have been utilized, although proof of their usefulness is lacking. A major step forward was achieved when peptide analogs of the GnRH were introduced, first those with superagonist properties and subsequently those acting as antagonists. Initially, the latter produced side effects preventing their routine utilization; eventually, this problem was overcome following the synthesis of cetrorelix. Because both types of analogs produce hypoestrogenism, their use is limited to a maximum of 6 months and, for this reason, today they are utilized as an adjuvant treatment before surgery with overall good results. Over the last decade, new, nonpeptidic, orally active GnRH-receptor blockers have also been synthesized. One of them, Elagolix, is in the early stages of testing in women with fibroids. Another fundamental development has been the utilization of the so-called selective progesterone receptor modulators, sometimes referred to as “antiprogestins”. The first such compound to be applied to the long-term treatment of fibroids was Mifepristone; today, this compound is mostly used outside of Western Countries, where the substance of choice is Ulipristal acetate. Large clinical trials have proven the effectiveness of Ulipristal in the long-term medical therapy of fibroids, although some caution must be exercised because of the rare occurrence of liver complications. All selective progesterone receptor modulators produce unique endometrial changes that are today considered benign, reversible, and without negative consequences. In conclusion, long-term medical treatment of fibroids seems possible today, especially in premenopausal women. Keywords: uterine myomas, progestin, gonadotropin-releasing hormone receptor blockers, selective progesterone receptor modulators, antiestrogens